انحراف الأحداث وواقع التدخل المهني من وجهة نظر الأحداث دراسة ميدانية في معاهد رعاية الأحداث بمدينة دمشق - عقيل, أديب; برقاوي, هناء; اسماعيل, رندا (Latakia University Journal - Arts and Humanities Sciences Series, 2013)
يرتبط الرفاه الاجتماعي والطمأنينة في أي مجتمع من المجتمعات ارتباطاً شديداً بمدى ما يقدم المجتمع من رعاية واهتمام لعلاج مشكلة الأحداث المنحرفين لأن مشكلة انحراف الأحداث تعد من أهم وأعقد المشكلات الاجتماعية التي تواجه جميع المجتمعات في العالم المعاصر المتقدمة منها أو النامية على حد سواء إذ يشهد هذا العصر تصاعداً مستمراً في انحراف الأحداث الذي يعد خسارة في التنمية البشرية من منظور اقتصادي واجتماعي معاً. فهو "قوى معطلة عن العمل والإنتاج، ويفسد جانباً من حياة الأسر والمجتمع وقد أشارت البحوث العلمية إلى أن الجريمة أكثر ما تكون شيوعاً بين الصغار، وأن معظم المجرمين البالغين بدؤوا حياتهم الجنائية منذ الحداثة، حيث اتضح أن 60% من المجرمين ارتكبوا جرائمهم الأولى قبل أن يبلغوا السادسة عشرة" (شفيق، 1996، 365). وتعد مؤسسات الرعاية الاجتماعية على المستوى النظري، الملاذ المؤسسي للأفراد الذين أصابتهم ظروفهم الأسرية والاجتماعية بأذى، بغض النظر عن درجة هذا الأذى وشدته. Social welfare and tranquility in any society is connected with the extent to which the society provides care and attention to solve the problem of juvenile delinquents. This is because the problem of juvenile delinquency is one of the most important and complex social problems facing all societies in the contemporary world, those developed or developing. This era is witnessing a growing increase in juvenile delinquency, which is considered a loss to human development from an economic and social perspective. It's "forces unable to work and produce, corrupting an aspect of the lives of the families and societies. Scientific research has pointed out that crime is most common among young adults and that most adult criminals started their criminal lives since adolescence, where it has been noticed that 60% of the criminals committed crimes before they were sixteen years old (Shafiq, 1996, P. 365). Theoretically speaking, the social welfare institutions are considered the institutional shelter for individuals damaged by family and social circumstances, regardless of the extent or intensity of this damage. By vocational intervention we mean programs offered in the institutes to protect juvenile delinquents who have been damaged by social or psychological circumstances, and rehabilitate them.